2003
DOI: 10.1002/sia.1534
|View full text |Cite
|
Sign up to set email alerts
|

Static SIMS analysis of carbonate on basic alkali‐bearing surfaces

Abstract: Carbonate is a somewhat enigmatic anion in static secondary ion mass spectrometry (SIMS) because abundant ions containing intact CO 3 2− are not detected when analyzing alkaline-earth carbonate minerals common to the geochemical environment. In contrast, carbonate can be observed as an adduct ion when it is bound with alkali cations. In this study, carbonate was detected as the adduct Na 2 CO 3 ·Na + in the spectra of sodium carbonate, bicarbonate, hydroxide, oxalate, formate and nitrite and to a lesser extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Because the molecular weight of K 2 CO 3 matches the 138 g mol –1 molecular weight observed, we also considered the possibility of carbonate contamination affecting the data. Shaw et al observed carbonate-containing ions in their static SIMS experiments from sodium salts with no carbonate, such as NaOH, NaC 2 O 4 , etc . They attributed this to the absorption of CO 2 from the atmosphere .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the molecular weight of K 2 CO 3 matches the 138 g mol –1 molecular weight observed, we also considered the possibility of carbonate contamination affecting the data. Shaw et al observed carbonate-containing ions in their static SIMS experiments from sodium salts with no carbonate, such as NaOH, NaC 2 O 4 , etc . They attributed this to the absorption of CO 2 from the atmosphere .…”
Section: Resultsmentioning
confidence: 99%
“…Shaw et al observed carbonate-containing ions in their static SIMS experiments from sodium salts with no carbonate, such as NaOH, NaC 2 O 4 , etc. 72 They attributed this to the absorption of CO 2 from the atmosphere. 72 Furthermore, bicarbonate may also permeate through the Nafion membrane into the cathode compartment.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation